2011
DOI: 10.4314/ajfand.v11i5.70448
|View full text |Cite
|
Sign up to set email alerts
|

A survey of on-farm seed production practices of sorghum (<i>Sorghum bicolor</i> L. Moench) in Bomet District of Kenya

Abstract: Sorghum (Sorghum bicolor L. Moench) is one of the important cereal crops utilized worldwide for human food, animal feed and to a lesser extent as a raw material in commercial food industries. The crop is a strategic commodity for food security, particularly in harsh environments. In Kenya, sorghum is an important crop consumed in some parts of the country as a staple food. It is also a major source of income to small-scale farmers who are its major growers. In the past, its cultivation was concentrated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…This was reported in the baseline survey conducted in sorghum seed systems in Eastern Kenya which were found to be largely traditional, with farmers playing a major role in the selection and exchange of seeds (Muui et al, 2013). A study conducted on sorghum production systems in Bomet, Kenya, indicated that farmers played a great role in seed selection, exchange and movement (Ochieng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This was reported in the baseline survey conducted in sorghum seed systems in Eastern Kenya which were found to be largely traditional, with farmers playing a major role in the selection and exchange of seeds (Muui et al, 2013). A study conducted on sorghum production systems in Bomet, Kenya, indicated that farmers played a great role in seed selection, exchange and movement (Ochieng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Most small scale farmers who plant landraces crop varieties in sub-Saharan Africa use on-farm produced and saved seed whose quality is usually poor [20,21,22,23]. The informal seed system includes methods such as retaining seed on-farm from previous harvests to plant the following season and farmer-to-farmer seed exchange net works [24,20,25]. Seed quality is of basic importance for a good seedling establishment and crop development.…”
Section: Introductionmentioning
confidence: 99%
“…This was one reason why all the LSF who produced sorghum in this study used it as animal feed while the SSFs used it both as food and feed. A study be Ochieng et al, (2011) also reported that all the farmers interviewed acknowledged the adaptability of the crop in the region but its production was constrained by lack of its marketability. …”
Section: Benefits and Constraints Of Cultivating Sorghummentioning
confidence: 99%
“…The poor grain yields in sorghum were partly due to the SSFs consistent use of unimproved seed and cultivation on small parcels of land. Ochieng et al (2011) reported low sorghum grain yields ranging from 0.5 to 2.5 t ha -1 for 92% of the SSFs interviewed compared to the research potential yield of ≥ 4 t ha -1 . Most SSFs in sub-Saharan Africa who plant unimproved varieties (landraces) used on-farm produced and saved seed whose quality was usually poor (Ashiono et al, 2005).…”
Section: Benefits and Constraints Of Cultivating Sorghummentioning
confidence: 99%